Viscosity and fragility of confined polymer nanocomposites: a tale of two interfaces. Issue 17 (16th April 2019) - A, Nimmi Das; Begam, Nafisa; Ibrahim, Mohd; Chandran, Sivasurender; Padmanabhan, Venkat; Sprung, Michael; Basu, J. K.
Abstract : Viscosity and fragility are key parameters determining the processability and thermo-mechanical stability of glassy polymers and polymer nanocomposites (PNCs). Abstract : Viscosity and fragility are key parameters determining the processability and thermo-mechanical stability of glassy polymers and polymer nanocomposites (PNCs). In confined polymers, these parameters are largely dominated by the long relaxation times of the polymers adsorbed at the substrate–polymer interface. On the other hand, for polymer nanocomposites, the interface layer (IL) between the nanoparticles and the surrounding matrix chains often control not only the morphology and dispersion but also various parameters like viscosity and glass transition temperature. Confined PNCs, hence, present a unique opportunity to study the interplay of these two independent interfacial effects. Here, we report the results of X-ray scattering based dynamics measurements of PNC thin films, with a two IL width, unraveling the subtle interplay of these two interfaces on the measured viscosity and fragility. Coupled with coarse-grained molecular dynamics (MD) simulations, our experimental results demonstrate that the viscosity of the PNC films increases with both the IL width and the thickness of the polymer layer adsorbed at the substrate interface. However, while both pristine PS and PNCs with a higher IL width become stronger glasses, as estimated by their fragility, the PNC with a lower IL width shows an increase in fragility with increasing confinement. Our results suggest a novel method to control thermo-mechanical properties and stability of PNC coatings by independently controlling the two interfacial effects in athermal glassy PNCs.